Effects of temperature and salinity on the reproductive phases of Macrocystis pyrifera (L.) C. Agardh (Phaeophyceae) in the Magellan region (vol 31, pg 915, 2019) - Pablo Rodriguez, Juan; Terrados, J.; Rosenfeld, S.; Mendez, F.; Ojeda Villarroel, Jaime Andrés; Mansilla Muñoz, Andres Omar (My University, 2019)
The original version of this article unfortunately contained mistakes. Please see below necessary corrections: 1) In the Introduction section (2nd page, 3rd paragraph) that refers to the distribution of Macrocystis pyrifera, this should be: "In Chile, M. pyrifera is distributed from Arica to Cabo de Hornos and the Diego Ramirez Islands (Rozzi et al. 2017)" and not "In Chile, M. pyrifera is distributed from Valparaiso to Cabo de Hornos and the Diego Ramirez Islands (Rozzi et al. 2017)". 2) In TABLE 1, the value of salinity in summer for Skyring Sound is incorrect. The corrected Table 1 is now shown here.
Keywords: Macrocystis pyrifera